FRI0641 Wrist inflammation as assessed by magnetic resonance imaging is associated with patient-reported physical impairment, global disease activity and pain in early rheumatoid arthritis: long-term results from two randomized controlled trials. (15th June 2017) - Glinatsi, D; Baker, JF; Hetland, ML; Hørslev-Petersen, K; Ejbjerg, BJ; Stengaard-Pedersen, K; Junker, P; Ellingsen, T; Lindegaard, HM; Hansen, I; Lottenburger, T; Møller, JM; et al.
Abstract : Background: Studies in established rheumatoid arthritis (RA) have shown that radiographic progression is associated with increasing health assessment questionnaire (HAQ) score. However, most studies have failed to demonstrate this association at the early stage of the disease. In addition, little is known about how specific pathologies, e.g. joint inflammation, tenosynovitis and joint damage, contribute to different patient-reported outcomes (PROs). Objectives: To examine the association between MRI wrist inflammation and damage with PROs in patients with early RA. Methods: MRIs of the wrist and hand were obtained from 210 early RA patients participating in two investigator-initiated, randomized, controlled studies (CIMESTRA/OPERA), which aimed at achieving inflammatory control by use of conventional and/or biologic drugs combined with intra-articular injection of glucocorticoids. The image-sets were assessed according to the RA MRI scoring system (RAMRIS) for inflammation (synovitis, tenosynovitis, osteitis) and damage (bone erosions, joint space narrowing) at baseline (n=210), 1 (n=206) and 5 (n=113) years follow-up. Data from the two studies were pooled and assessed for associations between MRI features and HAQ, patient global visual analogue scales (VAS-PtGlobal) and VAS pain using Spearman correlation for status and change scores, univariate and multivariable linear regression analyses for change scores and generalized estimating equations for status and change scores. MRI features were further tested for trends against specific hand-related HAQ questions using the Jonckheere trend test. Results: MRI inflammation, but not damage, showed statistically significant associations with HAQ, VAS-PtGlobal and VAS pain for status and change scores, independently of swollen joint count and level of C-reactive protein. Synovitis and tenosynovitis were the MRI features most consistently associated with PROs, particularly VAS-PtGlobal and VAS pain (Table 1 ). MRI synovitis and tenosynovitis mean scores increased with the level of difficulty to cut meat and open a milk carton (p<0.01), and similar patterns were seen for other hand-related HAQ items. As an additional analysis, the metacarpophalangeal joints were included in the analyses, but this did not strengthen the associations between MRI pathology and PROs. Conclusions: MRI-assessed inflammation, but not damage, in the early RA wrist is associated with patient-reported physical impairment, global disease activity and pain, and the amount of wrist inflammation influences physical hand function. Disclosure of Interest: D. Glinatsi: None declared, J. Baker: None declared, M. Hetland Grant/research support from: BMS, AbbVie, Pfizer, UCB-Nordic, MSD, K. Hørslev-Petersen Consultant for: AbbVie and UCB, B. Ejbjerg: None declared, K. Stengaard-Pedersen: None declared, P. Junker: None declared, T. Ellingsen: None declared, H. Lindegaard: None declared, I. Hansen: None declared, T. Lottenburger: None declared, J. Møller: None declared, L. Ørnbjerg: None declared, A. Vestergaard: None declared, A. G. Jurik: None declared, H. Thomsen: None declared, T. Torfing: None declared, S. Bisgaard: None declared, M. Axelsen Grant/research support from: Abbvie, M. Østergaard Grant/research support from: Abbvie, BMS, Janssen and Merck, Consultant for: Abbvie, BMS, Boehringer-Ingelheim, Celgene, Eli-Lilly, Centocor, GSK, Hospira, Janssen, Merck, Mundipharma, Novartis, Novo, Orion, Pfizer, Regeneron, Schering-Plough, Roche, Takeda, UCB, and Wyeth